Globalisation, Policy and Comparative Research
XIV, 180 p. 26 illus.
Keywords: This book critically examines the overall interplay between comparative education discourses, globalisation, and education. It draws upon recent studies in relevant areas and explores conceptual frameworks and methodological approaches. It demonstrates the neo-liberal ideological imperatives of education and policy reforms, and illustrates the way the relationship between the State and education policy affects current models and trends in education reforms and schooling globally. Various chapters critique the dominant debates and the newly constructed and re-invented models of neo-liberal ideology in education. Using a number of diverse paradigms in comparative education research, ranging from critical theory to globalisation, the authors, by focusing on globalisation, ideology and democracy, examine both the reasons and outcomes of education reforms, policy change and transformation and provide a more informed critique on the Western-driven models of accountability, quality and school effectiveness.